2007
DOI: 10.1620/tjem.212.91
|View full text |Cite
|
Sign up to set email alerts
|

A Palatinose-Based Balanced Formula Improves Glucose Tolerance, Serum Free Fatty Acid Levels and Body Fat Composition

Abstract: Palatinose is a disaccharide present in honey, which has the characteristics of delayed digestion and absorption. We developed a palatinosebased balanced formula (PBF) and reported its beneficial effects on metabolic syndromerelated parameters in rats. To examine the effects of PBF in humans, we here conducted a crossover study using twenty-three subjects with impaired glucose tolerance. The subjects were divided into two groups: intervention to control (I/C) and control to intervention (C/I) groups. The I/C g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
4
17
0
1
Order By: Relevance
“…The differences in honey composition especially regarding the disaccharides seem to influence the effects of honey substantially. This was shown for palatinose, a disaccharide often present in honey (Oizumi et al, 2007). Perhaps similar mechanisms are also true for the fructose metabolism.…”
Section: Discussionsupporting
confidence: 58%
“…The differences in honey composition especially regarding the disaccharides seem to influence the effects of honey substantially. This was shown for palatinose, a disaccharide often present in honey (Oizumi et al, 2007). Perhaps similar mechanisms are also true for the fructose metabolism.…”
Section: Discussionsupporting
confidence: 58%
“…Besides, the comparison of both groups after completion of the training program (Table 2) reflects similar benefits: no differences in the parameters of exercise capacity and RPP peak , as well as in the resting cardiovascular parameters. We suppose that good control of diabetes and blood pressure in DM patients before they start any rehabilitation program contribute to a significant improvement in exercise capacity (Oizumi et al 2007). We are well aware of the fact that the benefit of rehabilitation in our study was enhanced by relatively low BMI in DM subjects.…”
Section: Discussionmentioning
confidence: 67%
“…As shown in many studies, sustained hyperglycemia is a risk factor for both micro vascular and macro vascular (as cardiovascular) complications in type 2 diabetes mellitus (Laakso & Lehto, 1997;Bretzel et al, 1998 as cited from Oizumi et al, 2007), while postprandial hyperglycemia has also been considered a risk factor for cardiovascular complications (Tominaga et al, 1999;Risso et al, 2001;Chiasson et al, 2002;Hanefeld et al, 2004;Nakagami et al, 2004 as cited from Oizumi et al, 2007). Many experimental and epidemiological studies have shown that increased postprandial plasma glucose levels may have equally or even more harmful effects than fasting hyperglycemia (Tominaga et al, 1999;Risso et al, 2001;Nakagami et al, 2004 as cited from Oizumi et al, 2007), and the reduction of postprandial plasma glucose levels delays the development of cardiovascular complications (Chiasson et al, 2002;Hanefeld et al, 2004 as cited from Oizumi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental and epidemiological studies have shown that increased postprandial plasma glucose levels may have equally or even more harmful effects than fasting hyperglycemia (Tominaga et al, 1999;Risso et al, 2001;Nakagami et al, 2004 as cited from Oizumi et al, 2007), and the reduction of postprandial plasma glucose levels delays the development of cardiovascular complications (Chiasson et al, 2002;Hanefeld et al, 2004 as cited from Oizumi et al, 2007). Jenkins (1987) defined the glycemic index as the ratio between the blood glucose areas produced after ingestion of a studied sugar compared to the blood glucose area produced after glucose ingestion itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation